Drivers of Financial Inclusion among Cocoa Producers in the Southwest Region of Cameroon - Ngwang, Norbert Ngoongeh; Bime, Mary-Juliet Egwu (Finance & Economics Review, 2023)
Purpose: Financial inclusion can considerably promote cocoa production and provide a buffer for the escape from poverty traps for cocoa-growing economies like Cameroon. However, the Southwest region of Cameroon still experiences a low level of cocoa production and poverty primarily due to financial exclusion. This article explores the drivers of financial inclusion in the region. Method: A stratified multistage sampling technique was used to survey 380 cocoa producers in the main cocoa-producing areas in the region through semi-structured questionnaires. Descriptive statistics were used to analyze the socio-economic variables and the probit model to analyze the drivers of financial inclusion, subject to the three major dimensions of financial inclusion; access to, use, and quality of financial services. Results: On average, the long distance of financial institutions (9.3 km), intermediate farm sizes (2.6 ha), and low annual income (1,125,863 FCFA) negatively influenced financial inclusion resulting in just 16.6% of farmers being financially included. The findings also revealed that financial inclusion is significantly enhanced by an increase in income, farm training, the closeness of formal financial institutions (FFIs), larger household size, and small-scale production at a 1% significance level, and more years of farming experience at 5%. Moreover, 51.3% of the major constraints to financial inclusion were accounted for by lack of collateral security, distant FFIs, and low income. Implications: Reducing the distance of FFIs by establishing more institutions with considerations on collateral, increasing income through extension services like farm training, and sound agronomic practices will enhance financial inclusion. Originality: The uniqueness of this study lies in the context of the socio-political crisis during which cocoa producers were interviewed and exploring how the crisis influenced financial inclusion through a host of factors. Moreover, besides just access to credit as considered by most studies in Cameroon, the current study considers the use and quality of formal financial services as well.